Combined Effect of Age and Sex on the Gonial Angle of Mandible in North-Indian Population. - Shilpa B; Srivastava SK; Sharma RK; Sudha C (Department of Surgery, UKM Medical Centre, 2014)
The gonial angle of mandible, commonly known as the mandibular angle contributes significantly to the cosmetic facial profile of a person. The present study was conducted to examine the combined effect of age and sex on the Gonial Angle (GA) of the mandible in a group of North-Indian population. For this purpose, 60 adult human orthopantomographs (dental panoramic radiographs), ranging from 35-65 years were selected and divided into six groups of five-year age interval each with equal number of males and females. These digitalized radiographs were printed on special photographic papers. Gonial angle was measured as the angle formed between the inferior mandibular border and the posterior ramus, using a protractor. The mean of right-sided and left-sided values of gonial angle was calculated for each radiograph. These measurements were analyzed for interactions with age and sex, using SPSS software (version no. 18). In males, the mean gonial angle values ranged from 114.8° ± 8.341° to 122.3° ± 8.722°. In females, the values ranged from 114.7° ± 5.227° to 122.65° ± 5.413°. Significant positive correlations (p<0.05) were calculated between age and gonial angle for both males (r=0.386) and females (r=0.403), as the mean gonial angle values showed an increase with increasing age in both the sexes. The female values recorded were higher than those of males in majority of the age groups. But sexual dimorphism was not observed. Therefore, the results of the present study concluded that age had a significant influence on the gonial angle but sex affected the gonial angle only to a certain extent.